Critical Reflections on Assessment Approaches in School Education Minimum Levels of Learning, Continuous and Comprehensive Evaluation and Learning Outcomes - Vandana; Masih, Aejaz (JOURNAL OF INDIAN EDUCATION, 2022)
Assessment being an inextricable part of any learning process has gone through many ups and downs since independence in India. Transformations have seen from the introduction of Minimum Levels of Learning: to measure a list of competencies as an end product, to the introduction of theoretically sound ‘Continuous and Comprehensive Evaluation (CCE): to guide the overall learning process of student. With time, many pitfalls and implementation failures have been observed in these approaches of assessment. Thus, the inception of learning outcomes approach after CCE’s unexpected implementation failure opens a scope for critical discourse in the field of school education in India. The term ‘learning outcomes’ reflects a conceptual tension and far less scope of flexibility as propounded by many educationists globally. Thus, the paper attempts to show the post-independence journey of school level assessment procedures in India and critically reflects upon the current learning outcomes approach from national and international perspective to predict its future feasibility and upshots.